Perluasan Kewenangan Pelaporan Majelis Pengawas Notaris: Diskursus Kepastian Hukum dan Keadilan Substantif - Fenny Tria Yunita; Malik Wahyu Kurniawan (Faculty of Law, University of Jember, Indonesia, 2021)
This paper aims to examine the new authority of the notary supervisory board in reporting an ethic and performance violations which committed by notary and its relation to the principles of certainty and justice. According to the Regulation issued by Minister of Law and Human Rights of the Republic of Indonesia number 15 of 2020 concerning The Procedures for Examination of the Notary Supervisory Board (MPN), the authority of MPN has being enlarged. This regulation give a bigger authority for MPN to report and make a report as the result of the implementation of notary’s occupation, so that the MPN can examine and make decisions according to their own report. Otherwise, the Notary Act (UUJN) only gives MPN an authority to examine and make decisions based on reports of people who have been violated by Notary. This can be seen in Article 73 paragraph (1) of the UUJN which states that